IDENTIFIKASI FUNGI PADA TAPE BERAS MERAH (ORYZA SATIVA GLABERRIMA) SERTA PERANANNYA SEBAGAI SUMBER BELAJAR BERUPA MODUL TERHADAP KETERAMPILAN MERENCANAKAN PERCOBAAN PADA POKOK BAHASAN FUNGI SISWA KELAS X SMA - Setyowati, Nining; Harlita, Harlita; Muzayyinah, Muzayyinah (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT - The purpose of this study was to (1) Identify the type of fungus found on red rice tape (Oryza sativa glabberima). (2) Determine differences in students the skills to plan experiments in teaching and learning process with additional learning resources in the form of modules results in the learning process without additional module on research results of class X SMA Al Islam 1 Surakarta. This study population is the entire class X SMA Al Islam 1 Surakarta odd semester of the academic year 2011/2012. The sample in this study were students in class X-7 as a control class and the class X-8 as a class experiment. Cluster sampling technique with Random Sampling. The results of biological research in the form of modules as independent variables and students' skills to plan the experiment as the dependent variable. Data collection techniques of the skills to plan an experiment using the documentation and observation sheet. Techniques of data analysis using t test. This study is a quasi-experimental studies (Quasi Experiment) using Randomized Control Design Only. The results of this study summed up as follows: (1) Fungi in the red rice tape involved in rice fermentation process found two genera of Saccharomyces and Aspergillus viewed from morphological features. (2) There are differences in students the skills to plan experiments in teaching and learning process with additional learning resources in the form of modules results in the learning process without additional module on research results of class X SMA Al Islam 1 Surakarta. Keywords: The Identification of Fungi, Skill For Planning A Research